2013
DOI: 10.1021/nn403080y
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Environmental Transformations of Copper-Based Nanomaterials

Abstract: Copper-based nanoparticles are an important class of materials with applications as catalysts, conductive inks, and antimicrobial agents. Environmental and safety issues are particularly important for copper-based nanomaterials because of their potential large-scale use and their high redox activity and toxicity reported from in vitro studies. Elemental nanocopper oxidizes readily upon atmospheric exposure during storage and use, so copper oxides are highly relevant phases to consider in studies of environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
220
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(227 citation statements)
references
References 88 publications
(256 reference statements)
6
220
0
1
Order By: Relevance
“…Highly aggregated Cu NPs have a reduced surface area, which decreases the dissolution rate. In simple salt solutions, dissolution rate was nCu(OH) 2 -b > nCu ≫ nCuO, and in all cases, the dissolution rate decreased as pH increased from 4 to 11 Wang et al, 2013). Dissolution of Cu NPs was enhanced at high IS in the presence of NOM due to additional complexation.…”
Section: Environmental Fate Of Cu Npsmentioning
confidence: 88%
“…Highly aggregated Cu NPs have a reduced surface area, which decreases the dissolution rate. In simple salt solutions, dissolution rate was nCu(OH) 2 -b > nCu ≫ nCuO, and in all cases, the dissolution rate decreased as pH increased from 4 to 11 Wang et al, 2013). Dissolution of Cu NPs was enhanced at high IS in the presence of NOM due to additional complexation.…”
Section: Environmental Fate Of Cu Npsmentioning
confidence: 88%
“…Furthermore, high intracellular calcium levels caused by NPs may also serve as an alternative mechanism for the activation of these mechanisms. 84 Domenech et al 85 found that IO MNPs are capable of inducing lysosome LMP in cells. Yang et al 86 used both acridine orange staining and transmission electron microscopy (TEM) images to confirm that the accumulation of carbon nanohorns (CNHs) in the lysosomes induced LMP.…”
mentioning
confidence: 99%
“…In previous studies, 25,32,33 copper ions and CuS particles have been proven to be able to catalyze the HS − oxidation under oxygen-presence conditions. Here a depletion of DO upon addition of copper ions or CuS-NPs generated from the sulfidation to Na 2 S solution was also observed.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The X (9.8 GHz)-band EPR analyses using an EMX-plus CW spectrometer (Bruker Biospin) and the spin-trap 5,5-dimethyl-1-pyrroline-N-oxide (DMPO, Sigma-Aldrich, U.S.A.) could show a relative reactive oxygen species (ROS) intensity by observing peak height. The analyses were performed following the method as previously described by Wang et al 25 Briefly, 10 mg/L copper particles or CuSO 4 were mixed with DMPO (100 mM) and H 2 O 2 (1 mM) in buffer for 20 min. The reaction was triggered by the addition of H 2 O 2 .…”
Section: −28mentioning
confidence: 99%
See 1 more Smart Citation